FROM THEORY TO PRACTICE, IDENTIFYING GAPS IN ISLAMIC INVESTMENT IN INDONESIA AND ITS IMPLICATIONS FOR INTERNATIONAL BUSINESS STRATEGY - Akhmad Yusup; Zia Firdaus Nuzula; Irma Yulita Silviany (Jurnal Manajemen dan Bisnis Performa, 2025)
In an era where ethical investment is gaining unprecedented traction, the potential of Islamic finance remains largely untapped, particularly in Indonesia, the world's largest Muslim-majority country. This study investigates the gaps in Islamic investment practices in Indonesia and their implications for international business strategy. The research aims to explore the discrepancies between theoretical frameworks of Islamic finance and their practical application, emphasizing the role of financial literacy, socio-cultural influences, and regulatory challenges. Utilizing a systematic literature review methodology, the study synthesizes existing literature to identify key themes and gaps in the current understanding of Islamic finance in Indonesia. The findings reveal a significant disconnect between the ideals of Islamic finance and their implementation, highlighting the necessity for enhanced financial literacy programs and a robust regulatory framework to foster investor confidence. Additionally, the study underscores the importance of aligning investment products with the cultural and ethical values of Indonesian investors. The implications of these findings are twofold: they contribute to the theoretical discourse on Islamic finance and provide practical recommendations for financial institutions and policymakers. This research serves as a foundational step toward a more nuanced understanding of Islamic investment in Indonesia, paving the way for future studies that address the identified gaps.